Fusarium wilt of banana: current update and sustainable disease control using classical and essential oils approaches - Ismaila, Abubakar Abubakar; Ahmad, Khairulmazmi; Siddique, Yasmeen; Abdul Wahab, Muhammad Aswad; Kutawa, Abdulaziz Bashir; Abdullahi, Adamu; Mohd Zobir, Syazwan Afif; Abdu, Arifin; Abdullah, Siti Nor Akmar (Elsevier, 2022)
Fusarium species were reported to produce biofilms. Biofilms are superficial societies of microbes bounded and endangered by being situated or taking place outside a cell or cells. The most destructive fungal diseases caused by phytopathogens are as a result of biofilms formation. Fusarium wilt of banana (Panama disease) is caused by a soil-borne pathogen called Fusarium oxysporum f. sp. cubense. Fusarium oxysporum occurs in a form of a species complex (FOSC) which encompasses a crowd of strains. Horizontal genetic factor transfer may donate to the observed assortment in pathogenic strains, while sexual reproduction is unknown in the FOSC. Fusarium wilt is a notorious disease on several crops worldwide. Yield loss caused by this pathogen is huge, and significant to destroy crop yields annually, thereby affecting the producer countries in various continents of the world. The disease is also resistant to various synthetic chemical fungicides. However, excessive use of synthetic fungicides during disease control could be lethal to humans, animals, and plants. This calls for alternative eco-friendly management of this disease by targeting the biofilms formation and finally suppressing this devastating phytopathogen. In this review, we, therefore, described the damage caused by Fusarium wilt disease, the concept of filamentous fungal biofilms, classical control strategies, sustainable disease control strategies using essential oils, and prevention and control of vegetables Fusarium wilt diseases.